Static and dynamic approaches to vowel shifting in the Digital Archive of Southern Speech - Renwick, M; Stanley, J (Acoustical Society of America, 2017)
Speech varies widely in the American South, but the region is argued to share features including monophthongization of upgliding diphthongs, convergence of certain front vowels via raising and lowering, and back-vowel fronting. We investigate the influence of speaker sex and ethnicity on vowel production using data from the Digital Archive of Southern Speech. This corpus of 64 linguistic interviews (372 hours, recorded 1968−1983) offers large amounts of data from individual speakers, whose semi-spontaneous nature reveals a more realistic portrait of phonetic variability than is typically available. Interviews of European- and African American speakers permit comparison of the Southern Vowel Shift with the African American Vowel Shift. We show using static, single-point static measurements and dynamic vowel trajectories that rates of front-vowel shifting differ across sexes and races; European American females typically show the most advanced shifts in front and back vowels. While rates of /aɪ/ monophthongization vary predictably across phonological contexts, this phenomenon is variably implemented and variable across speakers and states. Acoustic analysis of historical speech corpora offers perspective for modern sociophonetic studies, by providing a point of comparison to illuminate the development of modern regional variation, which will inform and enhance models of language change over time.